2016
DOI: 10.1371/journal.pone.0162101
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory CD4+ T-Cell Subsets and Anti-Citrullinated Protein Antibody Repertoire: Potential Biomarkers for Arthritis Development in Seropositive Arthralgia Patients?

Abstract: ObjectiveSeropositive arthralgia patients (SAP) are at high risk of developing rheumatoid arthritis (RA). This prospective study aimed to determine whether altered peripheral regulatory T-cells (Tregs) and defined subsets, besides a broadened anti-citrullinated protein antibody (ACPA) response, may qualify as biomarkers for RA development in SAP.MethodsThirty-four consecutive SAP were prospectively assessed every 6 months for minimally 2 years. At inclusion, peripheral Treg (CD4+CD25+FoxP3+) numbers and subset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
13
0
2
Order By: Relevance
“…CD4 + CD25 + FoxP3 + T cells (Treg) can suppress other immune cells by regulating their proliferation and cytokine production. No differences were detected in the number of total Treg and bona fide Treg subsets (CD45RA + FoxP3 low naïve Treg, CD45RA − FoxP3 high activated Treg, and CD45RA − FoxP3 low non-Treg) from seropositive arthralgia patients compared to healthy donors [ 27 ]. Whether Tregs are functionally different is still unknown [ 14 ].…”
Section: An Introduction To the Physiopathology Of Rheumatoid Arthmentioning
confidence: 99%
“…CD4 + CD25 + FoxP3 + T cells (Treg) can suppress other immune cells by regulating their proliferation and cytokine production. No differences were detected in the number of total Treg and bona fide Treg subsets (CD45RA + FoxP3 low naïve Treg, CD45RA − FoxP3 high activated Treg, and CD45RA − FoxP3 low non-Treg) from seropositive arthralgia patients compared to healthy donors [ 27 ]. Whether Tregs are functionally different is still unknown [ 14 ].…”
Section: An Introduction To the Physiopathology Of Rheumatoid Arthmentioning
confidence: 99%
“…The number of regulatory T cells (Tregs) in the peripheral blood appeared not to be indicative of RA development in patients with seropositive arthralgia. 30 In contrast, others showed that reduced naïve T cells and Tregs and increased inflammation-related cells were predictive of progression to arthritis in ACPA-positive persons with non-specific MSK symptoms. 49 Seropositive patients who developed arthritis had a significantly decreased number of peripheral CD8+ T cells and memory B cells compared with non-converters.…”
Section: Markers Characterising Immune Cell Dysfunctionmentioning
confidence: 98%
“… Patients in refs 22 31 36 37 52 54 55 , in refs 30 34 , in refs 27 49 and in refs 38 50 51 56 are derived from the same cohort. Studies depicted in grey have provided absolute risks.…”
Section: The Predictive Accuracy Of Non-antibody Serological Markers mentioning
confidence: 99%
“…In a study on patients with seropositive arthralgia, no differences were detected in the percentage and number of naïve CD4 + CD25 + FoxP3 + T cells compared with healthy controls. 10 The same was found for activated CD4 + CD25 + FoxP3 + T cells. Comparing the CD4 + CD25 + FoxP3 + T cells from patients with seropositive arthralgia who converted to patients with RA with those who did not resulted again in no detectable differences.…”
Section: Introductionmentioning
confidence: 52%